2022
DOI: 10.3899/jrheum.220023
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Plasma Microbiome: A Potentially New Perspective to the Dysbiosis in Systemic Lupus Erythematosus?

Abstract: The human microbiome, which consists of the microbial communities inhabiting the human body, has sparked growing excitement in both basic research and clinical practice.1,2 Gut microbiota, in particular, has been considered a major environmental factor in modulating immune responses in autoimmune diseases (ADs).3,4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Lupus is a systemic autoimmune disease, and we hypothesize that systemic microbial translocation of specific microbial types may play a more critical role in disease pathogenesis than measures of the microbiome from the surface barriers, such as the gut, skin, oral cavity, and genital areas. If our hypothesis is correct, analysis of SLE‐associated plasma microbiome alterations may provide novel insight into understanding systemic inflammation and disease pathogenesis in SLE 12 …”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Lupus is a systemic autoimmune disease, and we hypothesize that systemic microbial translocation of specific microbial types may play a more critical role in disease pathogenesis than measures of the microbiome from the surface barriers, such as the gut, skin, oral cavity, and genital areas. If our hypothesis is correct, analysis of SLE‐associated plasma microbiome alterations may provide novel insight into understanding systemic inflammation and disease pathogenesis in SLE 12 …”
Section: Introductionmentioning
confidence: 95%
“…If our hypothesis is correct, analysis of SLE-associated plasma microbiome alterations may provide novel insight into understanding systemic inflammation and disease pathogenesis in SLE. 12 Currently, there are limited reports of racial differences in plasma microbial translocation and the plasma microbiome in patients with SLE. A prior study reported blood levels of total microbial 16S DNA levels in the general population from 1,285 randomly recruited age-stratified individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation